Development of Filament Wound Composite Isotensoidal Pressure Vessels. Issue 3 (March 2014) - Zu, Lei; Koussios, Sotiris; Beukers, Adriaan; Zhang, Dinghua
Filament wound isotensoidal structures are recently gaining more attention for designing composite pressure vessels. In this paper we present the governing equation for creating geodesic-isotensoids based on the netting theory and geodesic winding law. The feasible intervals of the isotensoid-based design are also determined. The isotensoid-based dome profiles are determined by solving the governing equation with geometrical and initial winding conditions. When the applied axial load reaches a certain magnitude, the isotensoidal toroids can be obtained by forcing the isotensoid-based dome profile to become closed. The comparisons of the cross-sectional shapes between the isotensoidal dome and the hemispherical dome, and between the isotensoidal toroid and the circular toroid, are performed to demonstrate the preferable performance of the isotensoids. It is concluded that the isotensoid-based design leads to uniform fiber tension throughout the whole shell and the resulting structure can thus be considered as optimal for a pressure vessel. In addition, the isotensoid-based profiles show lower aspect ratios than the conventional vessel profiles under the given volume and internal pressure. Therefore the structural performance and the conformability to limited-height storage space of pressure vessels can be improved using the isotensoid-based design.